HUBUNGAN MOTIVASI MASYARAKAT BEROBAT DENGAN PEMILIHAN TEMPAT PELAYANAN KESEHATAN DI DESA PACE KECAMATAN SILO KABUPATEN JEMBER - Nurul Aini; Said Mardjanto; Firdha Novitasari (Jurnal Kesehatan dr. Soebandi, 2016)
Patients are motivated and trust to go to non-health care because non-health is considered capable of treating the disease. Non-health treatment A in 2012 increased about 30% from 2012 the number of visits reached 80 patients, reaching 104 patients in 2013. While non-health treatment B in 2013 experienced an increase of about 19% from 90 patients an increase of 107 patients. The purpose of this study was to determine the relationship of community motivation for treatment with the selection of health services. This study included a correlation study with a population of 960 households. The sampling technique uses simple random sampling technique that is the people who go to non-health workers are 96 families. The measured variable was the motivation of the community to seek treatment and the choice of health services. The results showed the motivation of medical treatment with moderate motivation was 68.8%, strong motivation was 20.8%, weak motivation was 10.4%. Whereas the community chooses non-health service providers 60.4% and 39.6% of health workers. From the results of the data analysis test using the Spearman Rank obtained p-value 0,000, at a significant level of p α (alpha) 0.05 so that Ho was rejected, which means there is a relationship between community motivation for treatment with the selection of health services in Pace Village, Silo District, Jember Regency in 2014 Where KK obtained 0.35 which has a moderate relationship.The advice given is the need to increase counseling activities about medical treatment and procedures for the management of Jamkesmas by health workers to improve the degree of community health in Pace Village